Why do Policy Makers stick to Inefficient Decisions? - Robert A.J. Dur (Tinbergen Institute, 1999)
This paper offers an explanation for why policy makers stick to inefficient policy decisions. I argue that repealing a policy is a bad signal to voters about the policy maker's competence if voters do not have complete knowledge about the effects of implemented policies. I derive the optimal policy maker's decision on continuation of a policy, assuming that voters' beliefs about the policy maker's competence are updated according to Bayes' rule. I show that if the policy maker cares sufficiently about reelection, he will never repeal a policy.
Keywords: 330; Politik; Entscheidung; Theorie